1973
DOI: 10.1073/pnas.70.6.1739
|View full text |Cite
|
Sign up to set email alerts
|

Hemogloblin Switching in Sheep and Goats: Erythropoietin-Dependent Synthesis of Hemoglobin C in Goat Bone-Marrow Cultures

Abstract: The anemia-induced switch from hemo. In eukaryotes, the molecular mechanisms involved in gene activation and in the subsequent production of specific cell proteins are largely unknown. To study gene activation in mammals, a cell population is needed that can be stimulated to transcribe the messenger RNA for a particular protein in response to a defined stimulus. We have studied the erythropoietin-dependent synthesis of hemoglobin C (HbC) in goat (and sheep) bone-marrow cultures for this purpose. Erythropoietin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1975
1975
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…These two hemoglobins are synthesized in the same cells and the control of this transition appears to be at the nuclear level, probably via transcription (3,18,33). This is in contrast to the mechanism for control of differentiation in species which shift from a primitive to a definitive cell line.…”
Section: Discussionmentioning
confidence: 55%
“…These two hemoglobins are synthesized in the same cells and the control of this transition appears to be at the nuclear level, probably via transcription (3,18,33). This is in contrast to the mechanism for control of differentiation in species which shift from a primitive to a definitive cell line.…”
Section: Discussionmentioning
confidence: 55%
“…Consistently, accumulation of ␤ C globin mRNA in response to intense Epo stimulation was previously described in anemic sheep 5 and in sheep bone marrow cultures. 17 Drugs that reactivate fetal erythropoiesis in human erythroid cell cultures, such as hydroxyurea, 5-azacytydine and butyrate, increase ␥-globin mRNA amounts. 16 In contrast, it has been shown that the compensatory increase of ␤min-globin chain synthesis in untreated ␤ thalassemic mice affects mRNA translation rather than accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…16 Increased ␤ C -globin mRNA amounts were also observed in anemic sheep 5 or in sheep bone marrow cultures stimulated with high doses of Epo. 17 It has been proposed that a more efficient translation of ␤min-globin mRNA than ␣-globin mRNA would account, at least partly, for the compensatory increase of ␤min-globin synthesis observed in ␤ thalassemic mice, in which serum Epo concentration is elevated. 18 However, how Epo improves the phenotype of ␤ thalassemic erythrocytes has not been directly investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…After an additional 24 h of incubation, the colonies were retrieved by trypsinization of the clots from 48 to 60 wells, washed, and lysed, and their products were analyzed by carboxymeth-ylcelluiose chromatography in 8 M urea phosphate buffer (3,16). To determine the pattern of globin synthesis in differentiating erythroid cells, bone marrow was placed directly in suspension culture and labeled between 0 and 11 h in vitro by addition of 300 /xCi of [aH]teucine (4). The cells were recovered and prepared for chromatography as previously described (16).…”
Section: Analysis Of Colony Number and Globin Synthesismentioning
confidence: 99%
“…As the animal matures, hemoglobin C synthesis ceases and is replaced by the adult hemoglobin; hemoglobin A (c~d32 A) in sheep and hemoglobin A, D, or E (containing flA, /3D, and /3 ~, respectively) in goats. In bone marrow cells of adult animals, hemoglobin C production can be reinitiated in vivo by anemic stress or injection of ESF (7,10,23) and in vitro by exposure to ESF (1,3,4).…”
mentioning
confidence: 99%